Inhibitory effect of Erinacines A on the growth of DLD-1 colorectal cancer cells is induced by generation of reactive oxygen species and activation of p70S6K and p21. (March 2016) - Lu, Chien-Chang; Huang, Wen-Shih; Lee, Kam-Fai; Lee, Ko-Chao; Hsieh, Meng-Chiao; Huang, Cheng-Yi; Lee, Li-Ya; Lee, Bih-O.; Teng, Chih-Chuan; Shen, Chien-Heng; Tung, Shui-Yi; Kuo, Hsing-Chun
Highlights: Erinacine A of Hericium erinaceus mycelium induces CRC cell cycle arrest. Erinacine A activates the mTOR/NFκB and p21 pathway. Erinacine A decreases the growth of CRC cells tumour xenograft in nude mice. Abstract: Hericium erinaceus is a well-known edible mushroom with valuable biological properties. Erinacine A is the major active agent of the diterpenoid compounds of the cultured mycelia of H.   erinaceus. This agent has multiple physiological activities, including anti-tumourigenic activity. In this study, we investigated the molecular mechanisms by which erinacine A mediated the generation of reactive oxygen species (ROS), and we performed cell cycle arrest to clarify molecular changes in colorectal cancer cells (CRC). Treatment of DLD-1 cells with erinacine A resulted in the phosphorylation of c-Jun N-terminal kinase (JNK) and p70S6K, the activation of p50 and p-IKB-β protein levels, the downregulation of cell-cycle-related proteins (cyclin A, cdk2, cyclin E, cdk4, and cyclin D1), and the induction of p21. Furthermore, treatment with the N -acetyl cysteine (NAC) and mTOR inhibitor (rapamycin) abolished erinacine A-induced cell cycle G1 arrest and reversed the association of CDK2 with Cyclin E and CDK4 with Cyclin D1. Therefore, when DLD-1 cells were grown as xenografts in nude mice, treatment with erinacine A induced a significant dose-dependent decrease in tumour growth. Histochemical and immunohistochemical analysis revealed that erinacine A treatment significantly reduced the number of mitotic cells. These results suggest that erinacine A presents an antitumour potential for CRC by inhibiting the growth of tumour cells in vitro and in vivo . Thus, we have identified a novel erinacine A-inhibited proliferation by activating p70S6K and ROS production, cell-cycle-related p21 proteins that provide a new mechanism for erinacine A-inhibited cell growth in human CRC.